THE INFLUENCE OF SERVICE QUALITY AND PRODUCT QUALITY ON CONSUMER SATISFACTION WITH PURCHASING DECISIONS AS INTERVENING VARIABLES AT ALFAMIDI DIPONEGORO TELUK DALAM-NIAS SELATAN - Paskalis Dakhi (Jurnal Ekonomi, 2023)
Consumer satisfaction is a person's feelings after consuming a product or service and compared to their expectations. Consumer satisfaction can be influenced by Service Quality, Product Quality and Purchasing Decisions. The research objective was to determine the direct and indirect effects of service quality, product quality and purchasing decisions on consumer satisfaction. This research was conducted on Alfamidi consumers, Jl. Diponegoro, Teluk Dalam, South Nias Regency. The data analysis technique used is path analysis. The population is Alfamidi Diponegoro consumers and the sample is part of the population using a probability sampling design with simple random sampling technique. The sample size is 119 people. Based on the analysis of the sub-structural equation model 1, it is evident that service quality and product quality influence consumer purchasing decisions. In sub-structural equation 2, it is proven that service quality, product quality and consumer purchasing decisions have an effect on consumer satisfaction.